2007
DOI: 10.1038/sj.ejhg.5201842
|View full text |Cite
|
Sign up to set email alerts
|

Differential haplotypic expression of the interleukin-18 gene

Abstract: Interleukin 18 (IL-18) is suspected to play an important role in atherosclerosis and plaque vulnerability. We had previously shown that haplotypes combining two IL18 gene polymorphisms in complete linkage disequilibrium, C-105T (rs360717) in 5 0 -untranslated region (UTR) and A þ 183G (rs5744292) in 3 0 -UTR, were related to IL-18 circulating levels and cardiovascular outcome, the C À105 G þ 183 haplotype being associated with lower IL-18 levels and lower cardiovascular risk. This study was aimed at investigat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
3

Year Published

2007
2007
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 30 publications
0
22
3
Order By: Relevance
“…Cloning and gene expression analysis have shown that two IL-18 gene promoter SNPs at positions -607 and -137 could cause differences in transcription factor binding and have an impact on IL-18 gene activity, as well as a potential effect on IFN-c [26]. A recent report showed that haplotypes associated with lower IL-18 circulating concentrations were consistently associated with decreased levels of expression of IL-18 [27].…”
Section: Discussionmentioning
confidence: 99%
“…Cloning and gene expression analysis have shown that two IL-18 gene promoter SNPs at positions -607 and -137 could cause differences in transcription factor binding and have an impact on IL-18 gene activity, as well as a potential effect on IFN-c [26]. A recent report showed that haplotypes associated with lower IL-18 circulating concentrations were consistently associated with decreased levels of expression of IL-18 [27].…”
Section: Discussionmentioning
confidence: 99%
“…IL-18 is expressed by epithelial cells of the amnion, chorionic cells, and decidual cells but not by syncytiotrophoblasts of the villi, and altered IL-18 levels have been linked to increased RSM risk (10)(11)(12)21). Insofar as IL-18 promoter singlenucleotide polymorphisms (SNPs) are associated with differential expression of IL-18 (22), this suggests a genetic susceptibility of RSM based on IL-18 promoter variants or haplotypes. In this study, we evaluated rs1946519 (À656C/A), rs187238 (À137G/C), rs360718 (À119A/C), and rs360717 (À105G/A) IL-18 promoter SNPs by allelic discrimination (real-time polymerase chain reaction) in women with RSM and controls and identified specific 4-locus haplotypes associated with increased risk of RSM.…”
mentioning
confidence: 99%
“…Within the entire region of the IL-18 gene, neither nonsynonymous SNPs nor ones that may interfere with mRNA splicing have been discovered. By using a haplotypic approach in several cohort studies, however, global associations between IL-18 haplotypes and plasma IL-18 levels were observed [39,40], although haplotypes explained only 1.8% of the variability of IL-18 levels [41]. As for the A-T-T haplotype, unfortunately, there have been no studies investigating the direct association between the haplotype and IL-18 protein levels.…”
Section: Discussionmentioning
confidence: 99%